The information services of the World Health Organization Library a survey with implications on meeting the information needs of the users - Romero, Mary Ann C.; Cruz, Ma. Divina P. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1996)
This study was conducted: 1) to identify the information services utilized by the users of the library; 2) to determine the users' preferences and awareness of library services; 3) to determine the effectiveness of the library in providing the information services to the users; 4) to determine the effects of information needs on library services; 5) to determine how the users rate the library; and 6) to identify problem areas for improvement.
The descriptive method of research was used for this study. Survey questionnaires were distributed personally to the library's clientele. A total of 170 questionnaires were distributed to the library's users. There were 141 respondents to the survey. Among the respondents, 137 were outside researchers and four were staff members.
The reference service was identified as the best service ranked by 26 respondents and the photocopying service ranked second with 23 respondents. However, the latter was the most ranked library service indicating the high rate of awareness and use of this particular service. The services provided by the library were rated good and the collection was rated the same by 44.7 of the respondents. It revealed that the library effectively provided the services needed by the respondents to their satisfaction. The respondents noted that the areas for improvement exist in the library facilities. The library has to be expanded to accommodate the growing collection and provide enough space for researchers. The expansion would also involve more participation on the part of the library staff, through extending more services to outside researchers. Local publications are endorsed by the respondents and researcher as additional research material for the library.
Typescript.
Vita.
Thesis (Bachelor of Library Science)
Keywords: Information services -- Philippines -- Manila; World Health Organization Library